2016
DOI: 10.1002/lno.10459
|View full text |Cite
|
Sign up to set email alerts
|

Climate warming and changes in Cyclotella sensu lato in the Laurentian Great Lakes

Abstract: We present the first evidence of biological change in all of the pelagic Laurentian Great Lakes associated with recent climatic warming. We hypothesized that measured changes in lake temperature, and the resulting physical changes to water columns, were affecting diatom communities in the Great Lakes. A paleolimnological analysis of 10 sediment cores collected from deep locations throughout the Great Lakes basin indicates a recent (30-50 yr) reorganization of the diatom community to one characterized by elevat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(28 citation statements)
references
References 44 publications
2
26
0
Order By: Relevance
“…in the sediment record (reviewed in Rühland et al ). Yet, the identification of specific mechanisms responsible for correlations of diatom abundances with ice‐out date (Wiltse et al ) or the duration of spring mixing (Kienel et al ) has been elusive (Smol et al ; Reavie et al ; Malik et al ; Warner et al ). In most previous studies, data collection did not begin until after ice‐out and/or did not couple sediment trap data with concurrent monitoring of chemical and biological variables in the water column, making potential links to processes during the ice‐covered period impossible to detect.…”
Section: Discussionmentioning
confidence: 99%
“…in the sediment record (reviewed in Rühland et al ). Yet, the identification of specific mechanisms responsible for correlations of diatom abundances with ice‐out date (Wiltse et al ) or the duration of spring mixing (Kienel et al ) has been elusive (Smol et al ; Reavie et al ; Malik et al ; Warner et al ). In most previous studies, data collection did not begin until after ice‐out and/or did not couple sediment trap data with concurrent monitoring of chemical and biological variables in the water column, making potential links to processes during the ice‐covered period impossible to detect.…”
Section: Discussionmentioning
confidence: 99%
“…The ecologies of these deep lake species have not been completely resolved; however, we generally consider the small Cyclotella and Discostella species to be members of the deep chlorophyll layer, i.e., associated with the thermocline [8,76,78]. In many northern lakes, their increased abundance is considered indicative of longer and more stable periods of stratification [1,76,79]. Others have also shown that the size structure within populations of these species may also reflect climate drivers [80].…”
Section: Diatom Community Shiftsmentioning
confidence: 99%
“…Sediment cores were collected from 10 locations throughout the Great Lakes, as detailed by Reavie et al [14]. Cores were age dated using 210 Pb, and details of those age models are provided by Reavie et al [15] (in review).…”
Section: Methodsmentioning
confidence: 99%
“…Because NCDC weather data did not give daily mean temperatures, the daily mean temperature was calculated by averaging daily minimum and maximum temperatures. Although we compiled these variations of temperature data, we ultimately selected analyses using annual minimum temperature due to its apparent dominant effect on phytoplankton communities in the Great Lakes [14] and because, worldwide, it is the most rapidly increasing temperature parameter [21]. The atmospheric deposition monitoring stations within 100 km distance from a given lake’s shoreline were selected to calculate loading relevant to that lake.…”
Section: Methodsmentioning
confidence: 99%